Jungian Reading: Exploring Mariner’s Self States through Individuation in The Rime of the Ancient Mariner - Aurora Magenta Diva; Asih Ernawati (LPPM Universitas Advent Indonesia, 2026)
This study presents a Jungian reading of Samuel Taylor Coleridge's “The Rime of the Ancient Mariner”, focusing on the Mariner’s psychological transformation through the lens of individuation. Using close reading as the primary method, the analysis explores how the Mariner’s self-states align with Carl Jung’s key archetypes—such as the ego, shadow, anima, and Self—each representing different stages of the individuation process. The Mariner's journey from guilt and alienation, symbolized by the killing of the albatross, to spiritual reconciliation, as reflected in his blessing of the water snakes, mirrors Jung’s theory of integrating unconscious elements into consciousness. This interpretation provides a deeper understanding of the Mariner’s inner conflict and eventual self-realization, while also highlighting the value of applying Jungian psychology to literary analysis. The study underscores how symbolic journeys in literature can mirror the complex process of psychological individuation and self-discovery